Penentuan Alternatif Instalasi Pengolahan Air Limbah di Kelurahan Mekar Rahayu Kabupaten Bandung - Eka Wardhani; Fahrul Halomoan Siregar; Ardellia Salsabila; Farhan Dzaki Muhammad; Olivia Zahra Pujiastuti; Tike Mustika Indah; Athaya Zahrani Irmansyah (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The village of Mekar Rahayu was selected as the site for the design of a wastewater treatment plant in Margaasih District. This sub-district is located in the Citarum River Basin, which does not yet have a domestic wastewater management system. Domestic wastewater is discharged into septic tanks or into drainage canals, which eventually ends up in rivers. This requires efforts to plan a domestic wastewater management system, considering that the domestic sector is the largest contributor to the pollution load in the Citarum River. The aim of this research is to determine an appropriate domestic wastewater management system to be implemented in the village of Mekar Rahayu. The research method is field observation and planning with reference to the regulations in force in Indonesia. The results of the research on local communal wastewater management systems can be applied in this region. It is planned that 2 future community wastewater treatment plants will serve 25 out of 28 community units in this sub-district. 3 communes that do not fall within the service area of the treatment plant because the settlements are small and dominated by agricultural land, so they can still use the local system. The calculation results for the total domestic wastewater generation are 118.16 litres/second. Based on the analysis of land requirements, ease of operation and other things, the selected series of domestic wastewater treatment plants are bar screen units, collection tanks, grit chambers, equilibration ponds, activated sludge, sedimentation II and disinfection.